Marine alkaloid Monanchocidin a overcomes drug resistance by induction of autophagy and lysosomal membrane permeabilization - Dyshlovoy, Sergey A.; Hauschild, Jessica; Amann, Kerstin Ute; Tabakmakher, Ksenia M.; Venz, Simone; Walther, Reinhard; Guzii, Alla G.; Makarieva, Tatiana N.; Shubina, Larisa K.; Fedorov, Sergey N.; Stonik, Valentin A.; Bokemeyer, Carsten; et al. (Oncotarget, 2015)
Monanchocidin A (MonA) is a novel alkaloid recently isolated from the marine sponge Monanchora pulchra. The compound reveals cytotoxic activity in genitourinary cancers including cisplatin-sensitive and -resistant germ cell tumor (GCT) cell lines, hormone-sensitive and castration-resistant prostate carcinoma cell lines and different bladder carcinoma cell lines. In contrast, non-malignant cells were significantly less sensitive. MonA is highly synergistic with cisplatin in GCT cells. Induction of autophagy at lower and lysosomal membrane permeabilization (LMP) at higher concentrations were identified as the dominating modes of action. Cytotoxicity and protein degradation could be inhibited by 3-methyladenine, an inhibitor of autophagy. LMP was confirmed by loss of acridine orange staining of lysosoms and by release of cathepsin B. In conclusion, MonA exerts cytotoxic activity by mechanisms different from "classical" apoptosis, and could be a promising new compound to overcome resistance to standard therapies in genitourinary malignancies.
EVALuna2:25492